Transnational Buddhism and Ritual Performance in Taiwan - Cheng, Wei-Yi (Contemporary buddhism, 2020)
This paper will compare the ritual performance in two transnational Buddhist organizations in contemporary Taiwan in attempt to investigate the influencing factors in shaping transnational Buddhism. The traditions of both Buddhist organizations studied in this paper are foreign in Taiwan: one is of Sri Lankan Theravada tradition and the other is of Vietnamese Mahayana tradition. The ritual performance chosen for the discussion is commonly translated into English as "Ghost Festival", though as to be shown later, the translation is somehow inappropriate. I will provide the ethnographic accounts of the Ghost Festival performed by the two organizations for discussion and comparison. Two influencing factors emerge from the comparative study are the role of ritual participants and the perception of the sacred. My discussion will show how these two factors shape Buddhist discourse in transnational context.